Kadar Beta Karoten Dan Daya Terima Pasta TomatDengan Penambahan Tepung Maizena - Hapsari, Dimar Fitria, Pramudya Kurnia, STP, M.Agr, Eni Purwani, S.Si, M.Si (2016)
Introduction : Tomato is a fruit which easily to damaged and not durrable in fresh, so required processing to increase quality, storablity, dan the acceptibility. Tomato paste is oneway to proceed tomato. Cornstarch act as thickener from tomato paste which is usually used for thickener of tomato sauce in the home industry. Objective : To determine the effect of cornstarch addition and the acceptibility of tomato paste. Research methods : This research uses complete precipitate with 3 treatments and 2 remidials. Testing the concentration of beta carotene is using Carr-Price- Spektrofotometer method, while scoring the acceptibility of tomato paste is done by using organoleptic test method covering colour, flavour, taste, texture, and whole using rather trained panelists. Result : The result of One-Way ANOVA shows that there is a significant influence in addition of cornstarch towards beta carotene of tomato paste, colour, taste, texture, and whole, but there is no influence in flavour, while the result of the organoleptic test shows that the most favourite tomato paste is the tomato paste which uses the addition og 1 g of cornstarch. Conclusion : There was an influence in addition of cornstarch towards beta carotene, colour, taste, texture, and whole.